Does surgeon handedness or experience predict immediate complications after mastectomy? A critical examination of outcomes in a single health system. Issue 3 (25th August 2019) - Luvisa, Kyle; Fan, Kenneth L.; Black, Cara K.; Wirth, Peter; Won Lee, Dong; Del Corral, Gabriel; Willey, Shawna C.; Song, David H.
Abstract: Surgeons often seek to perfect their technical dexterity, and hand dominance of the surgeon is an important factor given the constraints of operative field laterality. However, experience often dictates how surgeons are able to compensate. While surgeons have experienced preference for the ipsilateral breast, the impact of surgeon handedness, experience, and volume has not been directly examined in a single study. A retrospective chart review of five breast surgeons (2 LHD) at a single institution identified 365 mastectomy patients, totaling 594 breasts, between January 2015 and June 2018. The breasts were identified as ipsilateral or contralateral based on the surgeons' handedness. Surgeons were grouped based on length of surgical experience, three with ≥15 years and two with <15 years. Surgeons with greater experience were the highest volume surgeons in this series. Data included patient demographics, breast and oncologic history, surgical techniques, and surgical outcomes including complications. A total of 270 nonprophylactic and 324 prophylactic mastectomies were identified, of which 529 were performed by surgeons with greater than 15 years of experience and 65 by surgeons with less than 15 years. The overall complication rate was 33.5% (n = 199), of which 18.0% (n = 107) were on the ipsilateral breast and 15.5% (n = 92) were on the contralateral breast. 9.1% of complications required re‐operation (n = 54). The odds of any complication on the ipsilateral breast were 2.9 times higher than complications on the contralateral breast when looking exclusively at surgeons with <15 years of experience ( P  = .0353, OR = 2.92, 1.06‐8.03). Surgeons with <15 years of experience have a 2.71 ( P  = .05, OR 2.71, 1.361‐5.373) increase in any ischemic complication and a 16 times ( P  < .0001, OR = 16.01, 5.038‐50.933) increase in major operative ischemic complications. Our study finds that surgeons with less than 15 years of surgical experience have a 2.9 times higher rate of overall complication when operating on the ipsilateral breast. However, years of experience and surgeon volume have a much greater impact on any and ischemic complications after mastectomy.